Ultra-wideband pulse shaper for in-band interference mitigation. - Khatun, Sabira; Saeed, Rashid Abdelhaleem; Mohd Ali, Borhanuddin; Abdullah, Mohd Khazani; Ng, Chee Kyun (2007)

(untitled)
The present invention relates in general to an ultra wideband pulse shaper for in band interference mitigation characterized in that wherein a flat frequency spectrum of the transmitted signal over the bandwidth of the pulse is obtained by avoiding a dc component and wherein a desired frequency spectrum of the monocycle waveform is designed to be flat over a target bandwidth and wherein gaussian waveform pulses are used due to the flexibility and low computation process in the pulse generation in a receiver.